ANALISIS PERBEDAAN PARADIGMA PEMBANGUNAN EKONOMI KONVENSIONAL DENGAN EKONOMI ISLAM - Sabilla, Izma; Nabila, Salsa; Amelia, Balqis Hana (Institut Agama Islam Negeri (IAIN) Ternate, 2023)
This research has the title analysis of the sharia economic development paradigm and conventional economic development. This research uses a library study of the differences between the sharia economic development paradigm and conventional economics. The method used is the descriptive method, where this analytical method examines a group of people, objects, conditions, events in the present. Economics studies behavior that has no boundaries which originates from mutually agreed rules, while sharia economics is limited by sharia provisions which are sourced only from the Koran and Hadith. a paradigm that has an important role in the concept and implementation of development economics. Conventional economics only pays attention to changes that occur in economic variables, while sharia economics ignores economic variables and avoids things that cannot be justified in sharia.Keywords: Conventional Economics; Islamic Economics; Paradigm